Rare variation of the axillary artery - (:unkn) unknown (WILEY-LISS, 2000)
The third part of the axillary artery unilaterally divides into two major arterial stems, named according to their localization as deep brachial artery and superficial brachial artery (brachial artery). The deep brachial artery gives off the posterior circumflex humeral artery, anterior circumflex humeral artery, subscapular artery, and profunda brachii artery. It continues its course in the arm lateral to the median nerve and terminates by giving a minute twig to the radial artery. The superficial brachial artery is larger in caliber than the deep brachial artery and gives no branches in the arm region. In the cubital fossa it gives the ulnar and the radial arteries. This case is a variant of the axillary artery that has been rarely (0.12-3.2%) documented in the literature. Accurate knowledge of the normal and variant arterial anatomy of the axillary artery is important for clinical procedures in this region. Clin. Anat. 13: 66-68, 2000. (C) 2000 Wiley-Liss, Inc.
Keywords: axillary artery; superficial brachial artery; deep brachial artery